GLUTATION-S-TRANSPHERASE GENES POLYMORPHISM IN THE DIFFERENT ETHNIC GROUPS OF CHILDREN - E. V. Belyaeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The results of genotyping of blood samples of russian and buryat children on I/D polymorphism of GSTM1, GSTT1 genes by polymerase chain reaction are given. Absence of ethnic particularities in frequency deletion genotypes of GSTM1, GSTT1 genes is shown in this article.